Prognosis of 22- and 23-Gestational-Week-Old Infants at Our Facility: A Retrospective Cohort Study - Yanagisawa, Toshimitsu; Nakamura, Tomohiko; Kokubo, Masayo (American Journal of Perinatology, 2022)
Objective This study aimed to compare inborn infants aged 22 and 23 gestational weeks at our hospital to assess for differences in survival and long-term prognosis.Study Design We retrospectively analyzed 22- and 23-gestational-weeks-old infants born in our hospital between January 2011 and December 2018. The prognosis of inborn infants in Japan was also calculated using the Neonatal Research Network of Japan (NRNJ) data during the same period.Results The survival rates at our institution's neonatal intensive care unit discharge, including stillbirth, were 72 and 89% at 22 and 23 gestational weeks, respectively. The mortality rate and neurodevelopmental impairment (NDI) rate at 3 years of age, including stillbirth, were 58 and 32% at 22 and 23 weeks, respectively. Cerebral palsy, mental developmental retardation, visual impairment, and hearing impairment defined NDI. The prognosis at our hospital was better than the average calculated using NRNJ data. Survival rates varied among facilities, and some facilities had survival rates similar to that of our hospital.Conclusion The prognosis of 22-gestational-week-old inborn infants was inferior to that of 23 gestational weeks in our institution but was better than previously reported. If aggressive treatment is provided, survival without sequelae can be fully expected even for 22-gestational-week-old infants.Key Points
Keywords: extremely low birth weight; infant; mortality rate; neurodevelopmental outcome; survival rate